Vulnerability assessment of AP1000 NPP under mainshock-aftershock sequences. (1st April 2020) - Zhao, Chunfeng; Yu, Na; Peng, Tao; Gautam, Avinash; Mo, Y.L.
Graphical abstract: Highlights: The ED and ∇ IM considering aftershocks are considered into the fragility analysis. Four performance levels are proposed to evaluate the vulnerability of NPP. The probability of the AP1000 NPP containment structure is studied. Abstract: Researches explicitly indicate that the seismic events, consisting of the several shock waves (the first followed by the aftershock or train) may result in cumulative damage even if the intensity is not strong. This manuscript presents the vulnerability assessment formulation to estimate the influence of aftershocks on the damage of the nuclear power plant (NPP). In the formulation, the engineering demand ( ED ) parameter is derived. Four categories of performance levels (PL), three limit states (LS) and the relative intensity measure ( ∇ I M ) are defined to calculate the fragility of the AP1000 NPP under 30 groups of seismic sequences. The effect of aftershock and mainshock-aftershock ratio ∇ S a on the vulnerability of the structure are quantitatively analyzed. The observed results indicated that the aftershock can cause additional cumulative damage to the NPP. The fragility increases by 10–40% for different damage levels with an increase of ∇ S a from 0.5 to 1.0. The fragility framework can thus be used to assess the vulnerability of NPP under mainshock-aftershock sequences.